Analisis Pengaruh Kinerja Keuangan terhadap Zakat Perusahaan Asuransi Syariah - Tri Inda Fadhila Rahma; Ami Radianti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Sharia insurance is an effort to protect and help each other among policyholders which is carried out through the collection and management of tabarru funds that provide a pattern of returns to face certain risks through contracts that are in accordance with sharia principles. The aims of this study are (1) to understand the financial performance of Islamic insurance companies, (2) to understand the company's zakat, (3) to understand the effect of financial performance on Islamic insurance companies' zakat, and (4) to understand ROE and ROA. The research used in this research is quantitative deskriptive. The data is taken from secondary data, namely secondary financial statements. Hypothesis testing in this study uses regression analysis. In this study using the company's performance by using the ratio of ROE and ROA. The results of this study indicate that the company's performance using the ROE and ROA methods on the calculation of company zakat has a positive influence on company zakat, but all the results of the calculation can be concluded that insurance company zakat is influenced by the company's operational performance but not fully influenced by ROA and ROE, however. This could be a factor that influences the company in issuing its obligation to pay zakat. Keywords: Financial Performance, Corporate Zakat, Sharia Insurance